Stunting Following Moderate-to-Severe Diarrhea Among Children Aged <5 Years in Africa Before and After Rotavirus Vaccine Introduction: A Comparison of the Global Enteric Multicenter Study and the Vaccine Impact on Diarrhea in Africa (VIDA) Study. (19th April 2023) - Nasrin, Dilruba; Liang, Yuanyuan; Verani, Jennifer R; Powell, Helen; Sow, Samba O; Omore, Richard; Hossain, M Jahangir; Doh, Sanogo; Zaman, Syed M A; Jones, Joquina Chiquita M; Awuor, Alex O; Kasumba, Irene N; et al.
Abstract: Background: Studies conducted before rotavirus vaccine introduction found that moderate-to-severe diarrhea (MSD) in children aged <5 years was associated with stunting at follow-up. It is unknown whether the reduction in rotavirus-associated MSD following vaccine introduction decreased the risk of stunting. Methods: The Global Enteric Multicenter Study (GEMS) and the Vaccine Impact on Diarrhea in Africa (VIDA) study, two comparable matched case-control studies, were conducted during 2007–2011 and 2015–2018, respectively. We analyzed data from 3 African sites where rotavirus vaccine was introduced after GEMS and before starting VIDA. Children with acute MSD (<7 days onset) were enrolled from a health center and children without MSD (diarrhea-free for ≥7 days) were enrolled at home within 14 days of the index MSD case. The odds of being stunted at a follow-up visit 2–3 months after enrollment for an episode of MSD was compared between GEMS and VIDA using mixed-effects logistic regression models controlling for age, sex, study site, and socioeconomic status. Results: We analyzed data from 8808 children from GEMS and 10 579 from VIDA. Among those who were not stunted at enrollment in GEMS, 8.6% with MSD and 6.4% without MSD became stunted during the follow-up period. In VIDA, 8.0% with MSD and 5.5% children without MSD developed stunting. An episode of MSD was associated with higher odds of being stunted at follow-up compared with children without MSD in both studies (adjusted odds ratio [aOR], 1.31; 95% confidence interval [CI]: 1.04–1.64 in GEMS and aOR, 1.30; 95% CI: 1.04–1.61 in VIDA). However, the magnitude of association was not significantly different between GEMS and VIDA ( P = .965). Conclusions: The association of MSD with subsequent stunting among children aged <5 years in sub-Saharan Africa did not change after rotavirus vaccine introduction. Focused strategies are needed for prevention of specific diarrheal pathogens that cause childhood stunting. Abstract : Despite reductions in the attributable burden of rotavirus following vaccine introduction, the association between moderate to severe diarrhea and stunting at a 2–3 month follow-up did not change between studies conducted before and after rotavirus vaccine introduction at 3 sub-Saharan African sites.